Surgical Outcomes And Long-Term Complications Of Radical Cystectomy And Urinary Diversion In Bladder Cancer Patients (The Review of Diabetic Studies, 2025)
Background: Radical cystectomy (RC) with urinary diversion is the gold-standard treatment for muscle-invasive bladder cancer but is associated with significant morbidity and mortality. This systematic review synthesizes evidence on the surgical outcomes and long-term complications of this procedure, examining the impact of surgical technique, diversion type, and patient factors on survival, function, and quality of life (QoL).Methods: A systematic review was conducted following PRISMA guidelines. Databases (PubMed/MEDLINE, Embase, Scopus, Web of Science, CENTRAL) were searched for studies published between 2000-2025. Eligible studies included adults undergoing RC with urinary diversion, reporting on perioperative outcomes, complications, survival, or patient-reported outcomes. Data were extracted and synthesized narratively and, where appropriate, via pooled analysis. Risk of bias was assessed using standardized tools.Results: Nine studies were included. Perioperative outcomes varied widely; 30-day mortality was as high as 9.3% in high-risk cohorts like hemodialysis patients. Complication rates ranged from 43% to 91%, with major complications strongly predicting worse long-term survival. Minimally invasive, robot-assisted intracorporeal diversion (ICNB) was associated with fewer major complications compared to open techniques. Long-term overall survival was poor in high-risk groups (e.g., 12.1% at 5 years for dialysis patients), though cancer-specific survival was often preserved. Functional outcomes and QoL were heavily influenced by diversion type: neobladders were linked to worse urinary continence but less sexual bother, while ileal conduits were associated with greater psychosocial distress. Significant sex-specific issues were noted, including high rates of incontinence in women and erectile dysfunction in men. Long-term metabolic complications, including a 21% increased fracture risk, were also identified.Conclusion: RC with urinary diversion carries substantial risks for perioperative complications and long-term morbidity, which significantly impact survival and QoL. Outcomes are influenced by patient comorbidities, surgical approach, and choice of diversion. While enhanced recovery protocols and minimally invasive techniques improve short-term recovery, they do not consistently enhance long-term survival. Comprehensive, multidisciplinary survivorship care is essential to address the persistent medical, functional, and psychosocial challenges faced by patients